2016
DOI: 10.1270/jsbbs.15068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of proline concentration under osmotic stress in sunflower (<i>Helianthus annuus</i> L.)

Abstract: Proline concentration has been often suggested as an indicator of osmotic stress. A better understanding of the genetics of this trait is however needed. In the present study, proline concentration has been assessed, together with root and stem growth, potassium, calcium and total soluble sugars concentration and stress injury symptoms, in seedlings of sunflower hybrids and their parents grown under control and osmotic conditions. Proline strongly accumulated with osmotic stress. Its concentration exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…The highest proline accumulation occurred at the highest VAs concentration of 100 mg kg −1 . As reported in a previous study, the accumulation of proline in Medicago polymorpha and Medicago ciliaris under NaCl stress, was the greatest at the highest NaCl concentration of 100 mM [34]. Proline contributes to osmotic adjustment, stabilization, and protection of membranes integrity and macromolecules from the damage as a ROS scavenger [35,36].…”
Section: Secondary Experimentssupporting
confidence: 66%
“…The highest proline accumulation occurred at the highest VAs concentration of 100 mg kg −1 . As reported in a previous study, the accumulation of proline in Medicago polymorpha and Medicago ciliaris under NaCl stress, was the greatest at the highest NaCl concentration of 100 mM [34]. Proline contributes to osmotic adjustment, stabilization, and protection of membranes integrity and macromolecules from the damage as a ROS scavenger [35,36].…”
Section: Secondary Experimentssupporting
confidence: 66%
“…Proline concentration has been often suggested as an indicator of osmotic stress (Khalil et al, 2016). Proline accumulation under salt stress has been correlated with salt tolerance (Mansour and Ali, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, our result showed that there is a negative relationship of morphological traits (plant height, leaf area, fresh weight, dry matter and water contents) with proline accumulation in all sunflower cultivars (Table 6). Khalil et al (2016), stated that the negative relationship with morphological traits indicated that proline concentration may not be related with enhancing growth in sunflower but could increase survivability under stress contributing to the osmotic adjustment, and could participate in rapid recovery.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies regarding agronomic traits of sunflower are reported (Rauf, 2008); however, only few studies are conducted under drought stress (Casadebaig et al, 2008;Ghaffari et al, 2012;Pourmohammad et al, 2014;Khalil et al, 2016), and even less ones on drought under field conditions (Alza & Fernandez-Martinez, 1997). Most studies include only one or two cultivars.…”
Section: Teor De Prolina De Cultivares De Girassol No Semiárido Brasimentioning
confidence: 99%